Interlanguage Pragmatics of Request by IFL (Indonesian as a Foreign Language) Learners - Supriyanto, Ratih Asti (2016)
This study is an interlanguage pragmatics study on IFL (Indonesian as a Foreign Language) learners in expressing request strategies. This study was conducted toanalyze the requeststrategies used by IFL learners and NSI (Native Speaker of Indonesia), then to find the differences of them by using qualitative approach.This study also was conducted toanalyze the politenessstrategies used in requests by IFL learners and NSI. Subjects of this study are fifteen IFL learners and fifteen NSI. Data for this study is elicited from therespondents through the Discourse Completion Task (DCT) whichconsisted of nine situations with different levels of status. Therespondents in each group are asked to write the expression ofrequests to complete the DCT. Their responses are collected to beanalyzed based on the 8-level Trosborg's categories, and then also to be analyzed based on the politeness strategies by Brown and Levinson. The findings of the study show that most of the respondentsfrom the first group (IFL learners) utilized Conventionally Indirect (hearer-oriented condition) in theform of ability/willingness/ permission, followed by Direct request inthe form of imperatives, Combination Strategies, and Conventionally Indirect (speaker-basedcondition) in the form of needs/demands. But, the second group (NSI) mostly requested by using Direct request in the form of performative and imperative, followed by Conventionally Indirect (hearer-oriented condition) in theform of ability/willingness/ permission. It is also found that most of two of group participants used combination strategies of politeness in their requests.